Coronary Artery Calcium for Personalized Allocation of Aspirin in Primary Prevention of Cardiovascular Disease in 2019: The MESA Study (Multi-Ethnic Study of Atherosclerosis). Issue 19 (12th May 2020) - Cainzos-Achirica, Miguel; Miedema, Michael D.; McEvoy, John W.; Al Rifai, Mahmoud; Greenland, Philip; Dardari, Zeina; Budoff, Matthew; Blumenthal, Roger S.; Yeboah, Joseph; Duprez, Daniel A.; Mortensen, Martin Bødtker; Dzaye, Omar; et al.
Abstract : Background: Recent American College of Cardiology/American Heart Association Primary Prevention Guidelines recommended considering low-dose aspirin therapy only among adults 40 to 70 years of age who are at higher atherosclerotic cardiovascular disease (ASCVD) risk but not at high risk of bleeding. However, it remains unclear how these patients are best identified. The present study aimed to assess the value of coronary artery calcium (CAC) for guiding aspirin allocation for primary prevention by using 2019 aspirin meta-analysis data on cardiovascular disease relative risk reduction and bleeding risk. Methods: The study included 6470 participants from the MESA Study (Multi-Ethnic Study of Atherosclerosis). ASCVD risk was estimated using the pooled cohort equations, and 3 strata were defined: <5%, 5% to 20%, and >20%. All participants underwent CAC scoring at baseline, and CAC scores were stratified as =0, 1 to 99, ≥100, and ≥400. A 12% relative risk reduction in cardiovascular disease events was used for the 5-year number needed to treat (NNT5 ) calculations, and a 42% relative risk increase in major bleeding events was used for the 5-year number needed to harm (NNH5 ) estimations. Results: Only 5% of MESA participants would qualify for aspirin consideration for primary prevention according to the American College of Cardiology/American Heart Association guidelines and using >20% estimated ASCVD risk to define higher risk. Benefit/harm calculations were restricted to aspirin-naive participants <70 years of age not at high risk of bleeding (n=3540). The overall NNT5 with aspirin to prevent 1 cardiovascular disease event was 476 and the NNH5 was 355. The NNT5 was also greater than or similar to the NNH5 among estimated ASCVD risk strata. Conversely, CAC≥100 and CAC≥400 identified subgroups in which NNT5 was lower than NNH5 . This was true both overall (for CAC≥100, NNT5 =140 versus NNH5 =518) and within ASCVD risk strata. Also, CAC=0 identified subgroups in which the NNT5 was much higher than the NNH5 (overall, NNT5 =1190 versus NNH5 =567). Conclusions: CAC may be superior to the pooled cohort equations to inform the allocation of aspirin in primary prevention. Implementation of current 2019 American College of Cardiology/American Heart Association guideline recommendations together with the use of CAC for further risk assessment may result in a more personalized, safer allocation of aspirin in primary prevention. Confirmation of these findings in experimental settings is needed. Abstract : Supplemental Digital Content is available in the text.